Multilayer Satellite Network Dynamic Access Technology - Yunhan LI; Jianpeng MA; Xiongwen HE; Shun ZHANG; Hongyan LI (天地一体化信息网络)
Using the characteristics of satellites in diff erent orbits to build a more effi cient multilayer satellite network has become a hotspot in satellite network research in recent years.Traditional satellite network access methods have been unable to meet the needs of multilayer satellite networks with low latency and fl exible access, so it is urgent to design an effi cient random dynamic access protocol for multilayer satellite networks.This paper fi rst summarized the traditional satellite network access technology, clarifi ed the development context of the satellite network random access protocol, and then proposed diff erent low latency for the two diff erent scenarios of ground station access to satellite and multilayer satellite network intersatellite access.The access method could provided a reference for the development of the dynamic access technology of the multilayer satellite network in the future.